2011
DOI: 10.1021/jp203014j
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Blends Can Control Cationic Reversed Micellar Interdroplet Interactions. The Effect of n-Heptane:Benzene Mixture on BHDC Reversed Micellar Interfacial Properties: Droplet Sizes and Micropolarity

Abstract: We have investigated, for the first time, the effect of the composition of the nonpolar organic media on the benzyl-n-hexadecyl-dimethylammonium chloride (BHDC) reversed micelles (RMs) properties at fixed temperature. To achieve this goal we have used the solvatochromic behavior of 1-methyl-8-oxyquinolinium betaine (QB) as absorption probe and dynamic light scattering (DLS), to monitor droplet sizes, interfacial micropolarity, and sequestrated water structure of water/BHDC/n-heptane:benzene RMs. DLS results co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
142
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(160 citation statements)
references
References 62 publications
18
142
0
Order By: Relevance
“…To nd out the size and properties of the interface we studied water/BHDC/benzene:n-heptane RMs using dynamic light scattering (DLS) and the solvatochromism of 1-methyl-8-oxyquinolinium betaine (QB) at a xed temperature. 34 We demonstrated that the BHDC RM sizes and interfacial composition change upon n-heptane addition, as it was previously shown for AOT RMs with a nonpolar phase blend. 31 Thus, for BHDC RMs formed in benzene:n-heptane mixtures, droplet sizes, interfacial micropolarity and the water-polar head surfactant interaction increase as the n-heptane content increases.…”
Section: Introductionsupporting
confidence: 83%
“…To nd out the size and properties of the interface we studied water/BHDC/benzene:n-heptane RMs using dynamic light scattering (DLS) and the solvatochromism of 1-methyl-8-oxyquinolinium betaine (QB) at a xed temperature. 34 We demonstrated that the BHDC RM sizes and interfacial composition change upon n-heptane addition, as it was previously shown for AOT RMs with a nonpolar phase blend. 31 Thus, for BHDC RMs formed in benzene:n-heptane mixtures, droplet sizes, interfacial micropolarity and the water-polar head surfactant interaction increase as the n-heptane content increases.…”
Section: Introductionsupporting
confidence: 83%
“…[1] The amount of water dispersed in the organized system can be expressed by the ratio W 0 (W 0 = [Water]/[Surfactant]). BHDC forms RMs without the addition of cosurfactants [1][2][3][4][5] but CTAB needs the presence of a cosurfactant, usually an alcohol, to generate RMs. BHDC forms RMs without the addition of cosurfactants [1][2][3][4][5] but CTAB needs the presence of a cosurfactant, usually an alcohol, to generate RMs.…”
Section: Introductionmentioning
confidence: 99%
“…This IL-like surfactant was isolated from the original surfactant mixture (and elimination of NaCl) and showed properties absolutely different from Na-AOT and BHDC. [3,4,26] It is motivating to explore the interaction between the entrapped water and the interface formed by catanionic surfactants in RMs, in which both anionic and cationic polar head groups are present. Thus, we investigated its ability to form RMs in nonpolar solvents and spontaneous large unilamellar vesicles (LUVs) in water.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Salabat et al 21 used dynamic light scattering to monitor the apparent diffusion coefficient and effective microemulsion droplet diameter, and found that the interdroplet attractive interactions could be tuned by formulation of appropriate solvent mixtures using heptane, toluene, and dodecane. Myakonkaya et al 22 and Agazzi et al 23 also found that the properties of microemulsions and possibly also the droplet interaction can be controlled by changing the solvent blend composition. However, until now, no direct experimental evidence involving the solvent dependent enthalpy interactions between the microemulsion droplets has been reported to clarify the existence of some ambiguities and contradictories.…”
Section: Introductionmentioning
confidence: 98%